Growth hormone and insulin-like growth factor 1 affect the severity of Graves’ disease - Di Cerbo, Alfredo (Endocrinol Diabetes Metab Case Rep, 2017)
Graves’ disease, the most common form of hyperthyroidism in iodine-replete countries, is associated with the presence of immunoglobulins G (IgGs) that are responsible for thyroid growth and hyperfunction. In this article, we report the unusual case of a patient with acromegaly and a severe form of Graves’ disease. Here, we address the issue concerning the role of growth hormone (GH) and insulin-like growth factor 1 (IGF1) in influencing thyroid function. Severity of Graves’ disease is exacerbated by coexistent acromegaly and both activity indexes and symptoms and signs of Graves’ disease improve after the surgical remission of acromegaly. We also discuss by which signaling pathways GH and IGF1 may play an integrating role in regulating the function of the immune system in Graves’ disease and synergize the stimulatory activity of Graves’ IgGs. LEARNING POINTS: Clinical observations have demonstrated an increased prevalence of euthyroid and hyperthyroid goiters in patients with acromegaly. The coexistence of acromegaly and Graves’ disease is a very unusual event, the prevalence being <1%. Previous in vitro studies have showed that IGF1 synergizes the TSH-induced thyroid cell growth-activating pathways independent of TSH/cAMP/PKA cascade. We report the first case of a severe form of Graves’ disease associated with acromegaly and show that surgical remission of acromegaly leads to a better control of symptoms of Graves’ disease.